N′-[(1E)-(5-Nitrofuran-2-yl)methylidene]thiophene-2-carbohydrazide: crystal structure and Hirshfeld surface analysis - Cardoso, Laura N. F.; Nogueira, Thais C. M.; Wardell, James L.; Wardell, Solange M. S. V.; Souza, Marcus V. N. de; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
In the title carbohydrazide, C10H7N3O4S, the dihedral angle between the terminal five-membered rings is 27.4 (2)°, with these lying to the same side of the plane through the central CN2C(=O) atoms (r.m.s. deviation = 0.0403 Å), leading to a curved molecule. The conformation about the C=N imine bond [1.281 (5) Å] is E, and the carbonyl O and amide H atoms are anti. In the crystal, N-H...O hydrogen bonds lead to supramolecular chains, generated by a 41 screw-axis along the c direction. A three-dimensional architecture is consolidated by thienyl-C-H...O(nitro) and furanyl-C-H...O(nitro) interactions, as well as [pi]-[pi] interactions between the thienyl and furanyl rings [inter-centroid distance = 3.515 (2) Å]. These, and other, weak intermolecular interactions, e.g. nitro-N-O...[pi](thienyl), have been investigated by Hirshfeld surface analysis, which confirms the dominance of the conventional N-H...O hydrogen bonding to the overall molecular packing.